Flashing yellow lights on educational innovations - Torralba, Constantino M. (Education quarterly.)
Successful implementation of an educational innovation in any level ? community, regional, or national ? requires a well coordinated cooperative effort of all educators concerned. It is indispensable to pave the way with a favorable attitude of acceptance by the implementors, to prepare all personnel involved in the task, to help them in preparation and procurement of all necessary materials, and to see all possible loopholes, deficiencies, and weaknesses in orde to offer necessary preventive or remedial measures.